4. Решите уравнения: А) х2 – 7(х-4) = 28; Б) (5х-3)(3х-7) –х(3-5х)=0. СРОЧНО

4. Решите уравнения: А) х2 – 7(х-4) = 28; Б) (5х-3)(3х-7) –х(3-5х)=0. СРОЧНО
Гость
Ответ(ы) на вопрос:
Гость
Х^2 - 7( Х - 4 ) = 28 Х^2 - 7х + 28 - 28 = 0 Х^2 - 7х = 0 Х( Х - 7 ) = 0 Х = 0 Х - 7 = 0 Х = 7 Ответ 0 ; 7 ••••••••••••• ( 5х - 3 )( 3х - 7 ) - х( 3 - 5х ) = 0 15х^2 - 35х - 9х + 21 - 3х + 5х^2 = 0 20х^2 - 47х + 21 = 0 D = 2209 - 1680 = 529 = 23^2 X1 = ( 47 + 23 ) : 40 = 1,75 X2 = ( 47 - 23 ) : 40 = 0,6 Ответ 1,75 ; 0,6
Не нашли ответ?
Ответить на вопрос
Похожие вопросы